RANCANG BANGUN APLIKASI KOMUNITAS MANCING BERBASIS ANDROID - Saputra, Edo Halim; Arsa Suyadnya, I Made; Oka Widyantara, I Made (Jurnal SPEKTRUM, 2018)
This research intends to build an application that can be a place for members of the fishing community. The application is built on three main modules: user management, spot fishing management, and discussion management. Applications built using java programming language with android platform this application also uses API (Application Programming Interface) built with PHP programming language as interface processing data to database. Application testing is done by black box method and usability software, with the test result stated that the three main modules are running well and deserve to be used to be a means of information exchange for members of the fishing community.